What Determines Travel Intention during COVID-19 to Aceh, Indonesia? - Madjid, Iskandarsyah; Dinaroe, Dinaroe; Halim, Hendra (Universitas Syiah Kuala, 2024)
Objective This study intends to quantify the impact of tourist risk perception, tourist hygiene, and safety perception on the travel intention of tourists who visited Banda Aceh, Aceh Besar, Aceh Tengah, and Sabang, Indonesia, during the COVID-19 pandemic.Design/Methodology The purposive sampling method was used to collect primary data from respondents planning to travel to the specified destinations. 157 out of 175 distributed questionnaires were gathered. Moderated Regression Analysis (MRA) was employed to test the hypotheses.Results Tourist hygiene and safety perception significantly influence travel intention. Tourist risk perception significantly influences travel intention. Tourist risk perception does not moderate the influence of tourist hygiene and safety perception on travel intention.Research limitations/implications The study's findings suggest that governments of tourist destinations should ensure the availability of adequate facilities and infrastructure to promote travel intentions, particularly focusing on hygiene and security aspects. Limitations may include using purposive sampling, which might limit the generalizability of the results to a broader population.Novelty/Originality This study provides valuable insights into the relationship between tourist risk perception, hygiene, and safety perceptions on travel intentions during the COVID-19 pandemic, specifically in the context of Aceh's tourist destinations. The findings highlight the non-moderating role of tourist risk perception in the relationship between hygiene and safety perception and travel intention. This contributes to the existing literature on tourism and risk management during pandemics.